2015
DOI: 10.1002/lary.25527
|View full text |Cite
|
Sign up to set email alerts
|

Methylprednisolone use during radiotherapy extenuates hearing loss in patients with nasopharyngeal carcinoma

Abstract: Early sensorineural hearing loss after radiotherapy primarily affected the outer hair cells. The use of methylprednisolone during radiotherapy can extenuate early sensorineural hearing loss caused by irradiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 23 publications
0
1
0
1
Order By: Relevance
“…Conservative measures may include systemic steroids to improve inflammation and edema in the inner ear after radiation-induced damage and to reduce compression of the acoustic nerve due to inflammatory swelling. Chen et al [187] reported that the use of systemic methylprednisolone during RT can reduce early SNHL caused by irradiation. In a post-RT setting, Sakamoto et al [188] observed an improvement in hearing loss with oral prednisone, at least in young patients having a useful pretreatment hearing level, if the steroid treatment was administered immediately after the first detection of the hearing loss.…”
Section: Hearing Lossmentioning
confidence: 99%
“…Conservative measures may include systemic steroids to improve inflammation and edema in the inner ear after radiation-induced damage and to reduce compression of the acoustic nerve due to inflammatory swelling. Chen et al [187] reported that the use of systemic methylprednisolone during RT can reduce early SNHL caused by irradiation. In a post-RT setting, Sakamoto et al [188] observed an improvement in hearing loss with oral prednisone, at least in young patients having a useful pretreatment hearing level, if the steroid treatment was administered immediately after the first detection of the hearing loss.…”
Section: Hearing Lossmentioning
confidence: 99%
“…En adultos, la hipoacusia puede conllevar a una disminución de la calidad de vida 2,7 , cuya rehabilitación involucra un alto costo económico para los sistemas de salud 16 . Para prevenir la aparición de ototoxicidad se han intentado distintas estrategias incluyendo: la reducción de dosis durante los tratamientos combinados de QRT; dosis fraccionadas de RT, la RT de intensidad modulada, evitar incluir las estructuras auditivas en el campo de radiación 3 ; y estrategias farmacológicas para reducir el daño generado en células normales por estos tratamientos [17][18][19] , las que han presentado efectividad variable y la incertidumbre de que potencialmente puedan reducir la efectividad oncológica de estos tratamientos. En consecuencia, no existe ningún tratamiento farmacológico preventivo o terapéutico aprobado oficialmente para tratar este efecto adverso a la fecha, lo que ha sido motivo de creciente investigación en los últimos años.…”
Section: Introductionunclassified